Cataract surgery and age‐related macular degeneration. An evidence‐based update. (20th January 2015) - Kessel, Line; Erngaard, Ditte; Flesner, Per; Andresen, Jens; Tendal, Britta; Hjortdal, Jesper
Abstract Purpose Age‐related macular degeneration (AMD) and cataract often coexist in patients and concerns that cataract surgery is associated with an increased risk of incidence or progression of existing AMD has been raised. This systematic review and meta‐analysis is focused on presenting the evidence concerning progression of AMD in patients undergoing cataract surgery. Methods We performed a systematic literature search in the PubMed, Medline, Cochrane Library and CINAHL databases. Two randomized trials and two case–control trials were identified. Quality of the studies was assessed using the Cochrane risk of bias tool, data were extracted, and meta‐analyses were performed. Quality of the available evidence was evaluated using the GRADE system. Results We found that visual acuity at 6–12 months follow‐up was significantly better (6.5–7.5 letters) in eyes that had undergone cataract surgery than in unoperated eyes, but the included number of subjects was small, and hence, the quality of evidence was downgraded to moderate. We did not find an increased risk of progression to exudative AMD 6–12 months after cataract surgery [RR 3.21 (0.14–75.68)], but the included number of subjects was small, and thus, the quality of the evidence was moderate. Conclusion Cataract surgery increases visual acuity without an increased risk of progression to exudative AMD, but further research with longer follow‐up is encouraged.